The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/nu10111621
|View full text |Cite
|
Sign up to set email alerts
|

Docoxahexaenoic Acid Induces Apoptosis of Pancreatic Cancer Cells by Suppressing Activation of STAT3 and NF-κB

Abstract: The ω3-polyunsaturated fatty acid docosahexenoic acid (DHA) is known to induce apoptosis of cancer cells. In this study, DHA was shown to reduce viability of pancreatic cancer cells (PANC-1) by inducing DNA fragmentation, activating caspase-3, and increasing the ratio of Bax/Bcl-2. To determine the DHA mechanism of action, the impact of DHA on the activation of the key signaling proteins epidermal growth factor receptor (EGFR), signal transducer and activator of transcription factor 3 (STAT3), nuclear transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…DHA was also reported to enhance the oxaliplatin-induced decrease in cell viability and an increase in autophagy via ER stress/Sesn2 pathway in colorectal cancer cell lines both in vitro and in vivo [231]. DHA induced apoptosis of PANC-1 pancreatic cancer cells by suppressing the STAT3/ NF-κB -cyclin D1/survivin axis [232]. DHA inhibited proliferation and progression of A549 non-small cell lung cancer cells through ROS-mediated inactivation of the PI3K/Akt pathway [233], and also through the miR-138-5p/FOXC1 pathway in A549 and H1299 human lung cancer cell lines and LLC murine lung cancer cells [234].…”
Section: ω-3 Pufasmentioning
confidence: 96%
“…DHA was also reported to enhance the oxaliplatin-induced decrease in cell viability and an increase in autophagy via ER stress/Sesn2 pathway in colorectal cancer cell lines both in vitro and in vivo [231]. DHA induced apoptosis of PANC-1 pancreatic cancer cells by suppressing the STAT3/ NF-κB -cyclin D1/survivin axis [232]. DHA inhibited proliferation and progression of A549 non-small cell lung cancer cells through ROS-mediated inactivation of the PI3K/Akt pathway [233], and also through the miR-138-5p/FOXC1 pathway in A549 and H1299 human lung cancer cell lines and LLC murine lung cancer cells [234].…”
Section: ω-3 Pufasmentioning
confidence: 96%
“…Compounds that prevent post-translational modification of Ras and its plasma membrane targeting are likely to inhibit oncogenic Ras signaling [47,49]. Previous reports from our lab and others suggest that PUFAs alter the plasma membrane binding domains of Ras to disrupt signaling [26,39,40,52,53]. Since Ras proteins are central to several signaling cascades, downregulation of the RAS genes observed in the gene expression study and suppressing expression of all the Ras isoforms studied in the western blot analysis, are expected to impact critical oncogenic pathways.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, n-3 PUFAs induce apoptosis and suppress cell proliferation in KRAS -mutant-derived pancreas nestin-expressing HPNE- KRAS G12D cells both in vitro and in vivo by reducing AKT phosphorylation [ 28 ]. A recent paper reported that DHA promotes the cell apoptosis of PANC-1 pancreatic cancer cells by inducing DNA fragmentation, activating caspase-3, and increasing the ratio of Bax/Bcl-2 via downregulating STAT3/nuclear factor (NF)-κB/cyclin D1 signaling [ 29 ]. On the other hand, EPA treatment of adipocytes reduces adipocyte-secreted factors, thus inhibiting breast cancer cell inflammation and migration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%